Real-Time SARS-CoV-2 Genotyping by High-Throughput Multiplex PCR Reveals the Epidemiology of the Variants of Concern in Qatar. (November 2021) - Hasan, Mohammad R.; Kalikiri, Mahesh K.R.; Mirza, Faheem; Sundararaju, Sathyavathi; Sharma, Anju; Xaba, Thabisile; Lorenz, Stephan; Chemaitelly, Hiam; El-Kahlout, Reham A.; Tsui, Kin Ming; Yassine, Hadi M.; Coyle, Peter V.; et al.
Abstract: Complementing whole genome sequencing strategies with high-throughput multiplex RT-qPCR genotyping allows for more comprehensive and real-time tracking of SARS-CoV-2 variants of concern. During the second and third waves of COVID-19 in Qatar, PCR genotyping, combined with Sanger sequencing of un-typeable samples, was employed to describe the epidemiology of the Alpha, Beta and Delta variants. A total of 9792 nasopharyngeal PCR-positive samples collected between April-June 2021 were successfully genotyped, revealing the importation and transmission dynamics of these three variants in Qatar.